Penilaian Publik Terhadap Pemberkasan Arsip Elektronik Oleh ANRI (Arsip Nasional Republik Indonesia): Analisis Isi Media Sosial Youtube - Permatasari, Angela; Mecca, Ihtada Aufa; Tsaqib, Iqbal Muhammad; Alghifari, Muhammad Ezrie; Rasya, Sayyidah; Azizah, Tiara Indah; Ananda, Zuda (Prisani Cendekia Institute, 2025)
This study aims to analyze the representation of electronic records filing by the National Archives of the Republic of Indonesia (ANRI) through the social media platform YouTube. The study uses a qualitative approach with a literature review method. Data was collected through content analysis of educational videos uploaded by ANRI and observations of public responses to the video. The findings indicate that ANRI has successfully presented a structured and informative narrative about the process of electronic records filing in accordance with national standards, with high scores in narrative and competence aspects. However, the tone and institutional image still need improvement to be more communicative and appealing to the general audience. Factors influencing this representation include the strength of the narrative, institutional competence, formal tone, and ANRI’s image as a modern institution. Improvement efforts include enhancing visuals and adopting a more inclusive communication approach, as part of the strategy to support the modernization of national archival management in the digital era.